MiR-27a: A Novel Biomarker and Potential Therapeutic Target in Tumors - Li, Xingwang (J Cancer, 2019)
MicroRNAs (miRNAs) are endogenous, time sequencing, conserved and small non-coding RNA molecules (19-25 bp long) that regulate gene expression at the post-transcriptional level by binding to the partial sequence homology of the 3'-untranslated region of target messenger (m)RNA. The miRNA-27 family consists of miR-27a and miR-27b, which are transcribed from different chromosomes and different in nucleotide at the 3' end. It has been reported that miR-27a was located on chromosome 19 and played a vital role in tumor development. Increasing evidences support a vital role for miR-27a in modulating polymorphisms, tumorigenesis, proliferation, apoptosis, invasion, migration and angiogenesis. Apart from it, miR-27a could affect drug sensitivity, treatment of cancer and patients prognosis. The miR-27a could be an oncogene or a tumor suppressor in several types of cancer, including colon cancer, pancreatic cancer, breast cancer, bladder cancer and hepatocellular carcinoma. In this review, we discuss the role of miR-27a in tumor biology and clinical significance in detail and offer novel insights into molecular targeting therapy for human cancers.